Characterization of Surface Finish in Turning of AISI D2 Steel With TiAIN-coated WC Insert - Muhamad, Mohd Razali; Budi, Esmar; Md. Nizam, Ab. Rahman (2007)
Surface roughness of a machined part one of the main attribute to be considered in turning operation and is influenced by the machining parameters. This study investigated the influence of turning operation process parameters (feed rate, cutting peed, and depth of cut) LO the work-piece (AISI D2) surface roughness using Central Composite Design experimental approach. The turning operation was conduct d using CNC and WC insert with TiAIN monolayer coating. The investigation result indicated that the feed rate was the most influential parameter to the surface roughness of machined surfaces followed by the cutting speed. On its own depth of cut was not a significant parameter. However, the interaction analysis indicated that depth of cut has a significant degree of interaction with both cutting speed and feed rule, and it cannot be ignored. Based on the experimental data, a predictive equation was developed to relate machining parameters to the surface roughness using regression analysis of a quadratic polynomial model.